Pathogenic, Phylogenetic, and Serological Analysis of Group I Fowl Adenovirus Serotype 4 SDSX Isolated From Shandong, China - Yu, Guanliu; Wang, Yawen; Zhang, Minmin; Lin, Yun; Tang, Yi; Diao, Youxiang (Frontiers in Microbiology, 2018)
Hydropericardium hepatitis syndrome (HHS) caused by group I fowl adenovirus serotype 4 (FAdV-4) is an acute and infectious disease in fowl, particularly in broilers aged 3–5 weeks. In June 2015, a highly pathogenic disease outbroke in 25-40 day-old ducklings in Shandong province, characterized similar symptom to HHS. In order to determine the pathogenic mechanism of FAdV-4 (SDSX strain) in meat ducks. We divided 90 25-day-old Cherry Valley meat ducks into three groups (oral, subcutaneous, and control; 30 ducks in each group) and infected them with the virus. HHS, inclusion body hepatitis, and enlargement and hemorrhage of the spleen, kidney, lung, thymus, and brain were observed in FAdV-4-infected meat ducks. Histopathological changes were mainly characterized by severe fatty degeneration in the liver, basophilic inclusion bodies in hepatocytes, and vacuolation in the bursa. More importantly, viral DNA could be detected by quantitative real-time polymerase chain reaction in several viscera tissues (e.g., heart, liver, spleen) on the third day after infection. Notably, the livers of the two infected groups contained the highest concentration of viral DNA. In addition, immune responses were studied based on titer levels of the virus antibody and the levels of inflammatory cytokines interleukin (IL)-2 and interferon (IFN)-γ, and most levels were significantly upregulated, indicating that the host immune responses were activated early in infection. These findings increase our understanding of the pathogenicity of FAdV-4 (SDSX) in meat ducks and provide the foundation for further in-depth study of the pathogenic mechanism of this virus.